PVT-tolerant Current Reference Generation using different PTAT currents. (August 2017) - Siddiqi, Yasir; Jawed, Syed Arsalan; Ahmed, Naveed
Abstract: A PVT tolerant precision current reference generator using an all-PTAT approach in 150 nm CMOS process is demonstrated. Three different PTAT currents are generated; two from on-chip resistors with different temperature and correlated process coefficients, and the third using Bandgap circuit. Three different sets of process and temperature coefficients allow active cancellation by taking difference of the PTAT currents with the freedom to implement different current manipulation coefficients using ratioed current mirroring as opposed to passive resistor-mixing approaches. The measurement results demonstrate that the reference current achieves a spread of ±5% in its nominal value and a temperature coefficient of 130 ppm/°C when measurements are carried out for 21 die-samples along with supply-voltage and temperature variations. The complete design consumes 30 uA current to generate 10 uA reference current from a 1.8 V power supply. The additional circuitry to generate the reference current has a foot-print of 60 um × 60 um. A supporting mathematical framework is also presented to elaborate the overall behavior of the circuit.